Impact of the association capability on innovation in smes from developing countries - Vázquez Zacarías, Manuel Alexis; Lira Arjona, Alfonso López (UANL. Facultad de Contaduría Publica y Administración, 2014)
A stream of research on strategic management has focused on a firm’s competitive advantage as a result of participation in networks or alliances with other firms. The effect of a given interrelation is subject to diverse exogenous and endogenous factors pertaining to each implicated entity. As a means of estimating a firm’s potential for achieving a positive result from an inter-firm endeavor, this study presents a conceptual research rooted on the analysis of the association capability. Managerial implications rely on the ability of obtaining an alternative source of innovation, a critical factor for the achievement of business sustainability.